2020
DOI: 10.3390/ijms21030906
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Different Prebiotics on the Modulation of Gut Microbiota Composition and Function in Morbid Obese and Normal-Weight Subjects

Abstract: The gut microbiota remains relatively stable during adulthood; however, certain intrinsic and environmental factors can lead to microbiota dysbiosis. Its restoration towards a healthy condition using best-suited prebiotics requires previous development of in vitro models for evaluating their functionality. Herein, we carried out fecal cultures with microbiota from healthy normal-weight and morbid obese adults. Cultures were supplemented with different inulin-type fructans (1-kestose, Actilight, P95, Synergy1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 70 publications
(90 reference statements)
2
29
0
3
Order By: Relevance
“…Zhang Q et al have demonstrated that inulin decreases Desulfovibrio abundance, reducing LPS and IL-6 levels in mice models [ 83 , 84 ] . This inulin action is replicated in human clinical trials [ 85 , 86 ] .…”
Section: Nutritional Strategies Aimed At Improving Gut Dysbiosis and mentioning
confidence: 87%
“…Zhang Q et al have demonstrated that inulin decreases Desulfovibrio abundance, reducing LPS and IL-6 levels in mice models [ 83 , 84 ] . This inulin action is replicated in human clinical trials [ 85 , 86 ] .…”
Section: Nutritional Strategies Aimed At Improving Gut Dysbiosis and mentioning
confidence: 87%
“…In brief, seven independent pH-free batch fermentations were performed for each human donor. We used as a carbon source 0.3% (w/v) of the fructooligosaccharide 1-kestose (β-Food Science Co. Ltd., Japan) which in previous experiments demonstrated to be more fermentable than other fructooligosaccharides not just by bifidobacteria and other intestinal anaerobes but also by lactobacilli ( Nogacka et al, 2020b ). Bacterial strains were added at a final concentration of 1 × 10 8 CFU/mL to fecal cultures in bottles.…”
Section: Methodsmentioning
confidence: 99%
“…Different models of GIM-host interaction, such as co-cultivation of fecal samples or isolated GIM from different population groups or added with pro/prebiotics, with epithelial and/or immune cells, have been used ( Arboleya et al, 2015 ; Nogacka et al, 2018 , 2020a ; Richards et al, 2019 ). Interestingly, several of these studies have demonstrated differences in the response induced by microbiotas from different population groups ( Nogacka et al, 2018 , 2020a ) and between isolated GIM or among GIM added with probiotics or prebiotics ( Arboleya et al, 2015 ; Nogacka et al, 2020b ). These suggest that the inter-population differences on the gut microbiota may partly explain the high variability observed in the response to probiotics and the low correlation between in vivo and in vitro data.…”
Section: Introductionmentioning
confidence: 99%
“…After deposition, samples were immediately frozen at −20 °C and transported to the laboratory. For analyses, samples were thawed at room temperature (24 ± 2 °C), weighed, diluted 1/10 in sterile PBS and homogenized using a LabBlender 400 Stomacher (Seward Medical, London, UK) for 4 min; the DNA was extracted using the QIAamp DNA stool mini kit (Qiagen, Hilden, Germany) following previously described procedures [ 41 ]. 7500 Fast Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) and SYBR Green PCR Master Mix (Applied Biosystems) were used to achieve the quantification of bacterial populations, including the major bacterial groups present in the human gut ( Supplementary Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…7500 Fast Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) and SYBR Green PCR Master Mix (Applied Biosystems) were used to achieve the quantification of bacterial populations, including the major bacterial groups present in the human gut ( Supplementary Table S2 ). Procedure instructions were published elsewhere [ 41 ]. Fecal DNA extracts were analyzed and the mean quantity per gram of fecal wet weight was calculated for each bacterial group.…”
Section: Methodsmentioning
confidence: 99%